2023
DOI: 10.5194/acp-23-13769-2023
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution trapping in the Dresden Basin from gray-zone scale urban modeling

Michael Weger,
Bernd Heinold

Abstract: Abstract. The microscale variability of urban air pollution is essentially driven by the interaction between meteorology and urban topography, which remains challenging to represent spatially accurately and computationally efficiently in urban dispersion models. Natural topography can additionally exert a considerable amplifying effect on urban background pollution, depending on atmospheric stability. This requires an equally important representation in models, as even subtle terrain-height variations can enfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…HYCAMR combines the community model CAMx and the block-scale diffusion model R-LINE to estimate pollutant concentrations in the near-road environment, but does not take into account the emission factors of different roads (Parvez and Wagstrom, 2019). The CAIRDIO-Les large vortex model simulates micrometeorology and air pollution in the Dresden Basin, Germany (Weger and Heinold, 2023). The VEIN-MUNICH model was developed and applied to the road-dense city of Sã o Paulo, Brazil, to predict NOx emissions from road vehicles (Gavidia-Calderón et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…HYCAMR combines the community model CAMx and the block-scale diffusion model R-LINE to estimate pollutant concentrations in the near-road environment, but does not take into account the emission factors of different roads (Parvez and Wagstrom, 2019). The CAIRDIO-Les large vortex model simulates micrometeorology and air pollution in the Dresden Basin, Germany (Weger and Heinold, 2023). The VEIN-MUNICH model was developed and applied to the road-dense city of Sã o Paulo, Brazil, to predict NOx emissions from road vehicles (Gavidia-Calderón et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kurppa et al (2019) firstly evaluated the vertical variation of aerosol number concentration and size distribution in a simple street canyon without vegetation in Cambridge by embedding the sectional aerosol module SALSA2.0 (Kokkola et al, 2008(Kokkola et al, , 2018 into the large-eddy simulation model PALM (Maronga et al, 2020). Weger and Heinold (2023) assessed the impact of meteorology and urban topography on the microscale variability of urban air pollution by using LES and empirical orthogonal function (EOF) analysis for the Dresden basin. Their results showed that the model results are strong sensitive to atmospheric conditions, but generally confirm increased eBC levels in Dresden due to the topography.…”
mentioning
confidence: 99%